2017
DOI: 10.1177/1460458217720394
|View full text |Cite
|
Sign up to set email alerts
|

Women’s expectations and experiences regarding e-health treatment: A systematic review

Abstract: There is a gap in knowledge of women's perceptions of e-health treatment. This review aims to investigate women's expectations and experiences regarding e-health. A search was conducted in MEDLINE, EMBASE, CINAHL and PsycInfo in March 2016. We included articles published between 2000 and March 2016, reporting on e-health interventions. The initial search yielded 2987 articles. Eventually, 16 articles reporting on 16 studies were included. Barriers to e-health treatment were lower for women than barriers to fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 59 publications
4
46
0
3
Order By: Relevance
“…25,26 The successful use of eHealth in health promotion programmes depends on the motivation and support that people can receive. 27,28,44 The current health literature is limited regarding eHealth ethical issues, especially from the service users' and citizens' perspective. 20,21 This is an important gap in ethics research given the wide use and planned increases in the adoption of eHealth technology discussed earlier.…”
Section: Ethical Issues Of Ehealthmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 The successful use of eHealth in health promotion programmes depends on the motivation and support that people can receive. 27,28,44 The current health literature is limited regarding eHealth ethical issues, especially from the service users' and citizens' perspective. 20,21 This is an important gap in ethics research given the wide use and planned increases in the adoption of eHealth technology discussed earlier.…”
Section: Ethical Issues Of Ehealthmentioning
confidence: 99%
“…20,21 Earlier studies have found varying and disparate use of eHealth in specific areas of health, for example, in telehealth, [21][22][23] in mental health and eHealth technologies, [24][25][26] and in varying diagnoses such as urinary incontinence and diabetes. 27,28 However, the user perspective concerned with, for example, which health technology and services are needed, along with their acceptability and feasibility, has rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Accessibility and flexibility, social motives and an option for anonymity and confidentiality are common arguments for choosing digital options 4–10. A recent review also suggests that it may be easier to seek care and to incorporate the training into daily life when it is accompanied by the flexibility and anonymity that online delivery provides, and that some people even rated their relationship with the online therapist higher than their relationship with their ordinary therapist 6. However, web-based or digital management for musculoskeletal disorders have thus far not been studied to any great extent 11…”
Section: Introductionmentioning
confidence: 99%
“…Finally, TBIs may be especially suitable for reducing substance use risks among women of childbearing age. Studies show that women reported that the anonymity of TBIs helps them feel less embarrassment and fear of being judged (Verhoeks et al., ) and thus makes it easier for them to discuss their feelings and express themselves (Beattie et al., ).…”
mentioning
confidence: 99%